2003
DOI: 10.1053/jhep.2003.50023
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of outcomes and predictors of mortality in patients with hepatopulmonary syndrome undergoing liver transplantation

Abstract: The hepatopulmonary syndrome (HPS) occurs in a subgroup of patients with cirrhosis and results from intrapulmonary vasodilatation, which may cause significant hypoxemia. Liver transplantation has emerged as a therapeutic option for patients with HPS based on retrospective case series and reports. However, morbidity and mortality appear to be increased after transplantation for HPS, and no prospective studies evaluating clinical features that may predict poor surgical outcome are available. Therefore, we prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
233
3
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(253 citation statements)
references
References 16 publications
11
233
3
6
Order By: Relevance
“…There are 2 reasonable arguments and supporting data to suggest HPS should advance the priority to accomplish OLT, assuming comorbidity is minimal. First, HPS has been shown to have an independent adverse effect on mortality before liver transplantation, 11 and second, complete resolution of HPS frequently occurs in patients surviving the transplant hospitalization. 1,5,6 If the patient survives the immediate postoperative course (intensive care unit/ transplant hospitalization), there is a high likelihood of normalization of arterial oxygenation over time (many months) with little chance of recurrence of HPS.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 reasonable arguments and supporting data to suggest HPS should advance the priority to accomplish OLT, assuming comorbidity is minimal. First, HPS has been shown to have an independent adverse effect on mortality before liver transplantation, 11 and second, complete resolution of HPS frequently occurs in patients surviving the transplant hospitalization. 1,5,6 If the patient survives the immediate postoperative course (intensive care unit/ transplant hospitalization), there is a high likelihood of normalization of arterial oxygenation over time (many months) with little chance of recurrence of HPS.…”
Section: Discussionmentioning
confidence: 99%
“…HPS is defined as the presence of liver disease and/or PH and intrapulmonary vascular dilatation, resulting in an abnormal age-corrected alveolar-arterial oxygen gradient (partial pressure of oxygen [PaO2] of b80 mmHg, and an AaPO2 of N15 mmHg, or N20 mmHg in patients N64 years of age) [58]. A taxonomy of the severity of the HPS based on alterations in oxygenation is essential because severity influences survival and is useful in determining the timing and the risks of orthotopic liver transplantation (OLT) [59,60]. The pulmonary gas exchange abnormalities of HPS are characterized by hyperventilation and arterial deoxygenation that can be mild (PaO2 b 80 mmHg), moderate (PaO2 b70 mmHg), or severe (PaO2 b 60 mmHg) [58].…”
Section: Pulmonary Complications 261 Hepatopulmonary Syndromementioning
confidence: 99%
“…Although select, highly specialized centers have demonstrated good posttransplant outcomes in very severely hypoxemic patients with HPS 9, 52, in addition to the increased risk of posttransplant hypoxemia 10, studies have demonstrated increased overall posttransplant mortality in patients with a pretransplant PaO 2 ≤50 mmHg 7, 11, 53. These data, along with the expected decline in PaO 2 of 5.2–13.5 mmHg per year in patients with HPS 7, 9 coupled with expected delays to transplantation, form the basis for the UNOS MELD exception threshold of PaO 2 <60 mmHg in HPS.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Although liver transplantation (LT) is curative in HPS, these patients have an elevated postoperative complication rate 6, 7, 8, 9. In particular, “severe posttransplant hypoxemia,” defined as a need for 100% inspired oxygen (FiO 2 ) to maintain a saturation of ≥85% (out of proportion to any other concurrent lung process) 10, has been identified as a major complication leading to prolonged ICU stay and death in this population 6, 9, 10, 11, 12. Although survivors have a complete normalization of gas exchange over time, severe posttransplant hypoxemia occurs in 6–21% of HPS patients, carries a mortality of 45%, and accounts for the majority of peri‐operative deaths in this population 10.…”
Section: Introductionmentioning
confidence: 99%